Implementasi Pelatihan Mendeley untuk Mendukung Publikasi Ilmiah Guru SMA Sains Tahfidz Qur’an Al Ammar - Yayuk Yuliana; Ova Novi Irama; Wan Dian Safina; Fitriani Pulungan; Anugerah Anugerah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to improve the competence of Al Ammar Qur'an Tahfidz Science High School teachers in managing scientific work references through the use of the Mendeley application. Problems faced by partners include low digital literacy in the use of reference managers, manual citation and bibliography creation, and difficulties in adapting to journal style. The activity implementation method uses a participatory approach through workshops, demonstrations, direct practice, and intensive mentoring. Evaluation was carried out with pre-test and post-test instruments to measure the increase in understanding and skills of participants. The results of the activity showed a significant increase in all assessment aspects, namely understanding the concept of reference, mastery of Mendeley features, reference management, use of automatic citations in Microsoft Word, and bibliography preparation. The highest increase occurred in automatic citation skills with a score increase of 37 points. This activity not only improves teachers' technical competence in scientific writing but also strengthens digital literacy and readiness for publication in accredited national and reputable international journals. This program contributes to strengthening a technology-based academic culture in partner schools and supports the implementation of MBKM and the achievement of higher education's Key Performance Indicators